An Analysis of Learning Motivation of Children Whose Parents Are Divorced at SMP Negeri 1 Sungai Beremas, West Pasaman Regency - Selfi Yuniarti; Harisnawati Harisnawati; Waza Karia Akbar (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aims to analyze the learning motivation of children whose parents are divorced at SMPN 1 Sungai Beremas, West Pasaman Regency. Parental divorce is a family condition that can affect the emotional, social, and psychological aspects of children, thus impacting their learning motivation at school. This study used a descriptive qualitative approach with a purposive sampling technique. The research informants consisted of students whose parents are divorced, subject teachers, guidance and counseling teachers, and parents. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The results showed that parental divorce has different impacts on children's learning motivation. Some children experienced a decrease in learning motivation characterized by low concentration, lack of enthusiasm for learning, and the emergence of withdrawal due to emotional instability and reduced parental attention. However, some other children were able to maintain and even increase their learning motivation by using family conditions as a driving force for achievement. Factors supporting children's learning motivation after divorce include teacher support, a conducive school environment, and children's self-acceptance of their family situation. Thus, the learning motivation of children whose parents are divorced is not uniform, but is influenced by the child's psychological condition and support from the surrounding environment.